Performance Evaluation of Lime in Resisting Moisture Damage in Elvaloy-Modified Asphalt - Arifuzzaman, Md (Current Smart Materials (Discontinued), 2018)
Background: This paper addresses the moisture sensitivity of Elvaloy-Modified Asphalt (EMA) in the presence of lime using Atomic Force Microscopy (AFM). The performance of three different lime percentages was evaluated for three different levels of EMA. The lime-modified EMA was conditioned for dry and wet environments and finally tested using AFM. All the AFM tests were performed using functional groups of asphalt binder: ammin (NH3), methyl (CH3), carboxyl (COOH), and hydroxyl (OH). Differences of adhesion/cohesion forces for dry and wet samples indicated nano-scale moisture damage. Conclusion: The study found that an increase in percentage of lime from 0.5% results in incremental damage due to moisture. Similarly, for a specific percentage of lime, moisture damage decreases with increased percentage of elvaloy. The use of 0.5% lime with 1.5% EMA outperforms all other combinations in resisting moisture damage and is proposed as the recommended dose for practical purposes.
Keywords: asphalt binder